AB0103 Polymyalgia rheumatica has a nocturnal rise in plasma interleukin-6 which is almost completely suppressed by night time administration of modified-release prednisone. (23rd January 2014) - Zakout, S.; Clark, L.; Jessop, D.; Straub, R.H.; Kirwan, J.R.
Abstract : Background: Musculoskeletal stiffness in polymyalgia rheumatica (PMR) follows a circadian rhythm. In rheumatoid arthritis (RA) patients, a timed release tablet of prednisone taken at 10pm led to a significant decrease in morning stiffness which was correlated with decreased night time plasma IL-6 [1]. However, the effects of timed release glucocorticoids on morning stiffness and the circadian profile of IL-6 in PMR have not been investigated. Previous studies of cytokines in PMR only collected blood samples at one time point mainly in the morning, without specifying the exact timing [2]. Objectives: To determine whether IL-6 follows a circadian rhythm in patients with newly diagnosed untreated PMR, and to compare the effects of morning and night time glucocorticoids on overnight IL-6 and morning stiffness. Methods: 10 patients with newly diagnosed PMR were randomised to two treatment groups with either night time modified-release prednisone 7mg (Lodotra) or morning immediate-release prednisolone 7mg. Hourly blood samples over 24-hours were taken before (Night A) and after 2 weeks treatment (Night B) to measure plasma IL-6. Patients were then treated with morning prednisolone 15mg and after 2 weeks a single measurement of IL-6 was performed at 9am (Day C). Duration of morning stiffness was recorded on each occasion. IL-6 assays were performed in Germany using the MILLIPLEX MAP kit. Results: IL-6 showed a marked circadian variation in PMR, with a rise during the early hours of the morning which was partially suppressed by 7mg morning prednisolone and almost completely suppressed by 7mg night time prednisone (Figure 1a and 1b ). Night time prednisone reduced morning stiffness by 90% compared to 42% with the morning prednisolone (p=0.044, t-test, figure 1c ). Conclusions: PMR, like RA, has a marked circadian variation in plasma IL-6. Both IL-6 and symptoms of morning stiffness are suppressed more by night time low dose glucocorticoids. This observation raises the possibility that PMR may be controlled by lower doses of glucocorticoids given at night compared to current conventional morning treatment. References: Buttgereit, F., et al., Efficacy of modified-release versus standard prednisone to reduce duration of morning stiffness of the joints in RA (CAPRA-1): a double-blind, randomised controlled trial. Lancet, 2008. 371(9608): p. 205-214. Spies, C.M., et al., More Night Than Day - Circadian Rhythms in Polymyalgia Rheumatica and Ankylosing Spondylitis. Journal of Rheumatology, 2010. 37(5): p. 894-899. Disclosure of Interest: None Declared